ON THE NATURE AND DYNAMICS OF THE SEISMOGENETIC SYSTEM OF SOUTH CALIFORNIA, USA: AN ANALYSIS BASED ON NON-EXTENSIVE STATISTICAL PHYSICS - Efstathiou, A.; Tzanis, A.; Vallianatos, F. (Bulletin of the Geological Society of Greece, 2016)
We examine the nature of the seismogenetic system in South California, USA, by searching for evidence of non-extensivity in the earthquake record. We attempt to determine whether earthquakes are generated by a self-excited Poisson process, in which case they obey Boltzmann-Gibbs thermodynamics, or by a Critical process, in which long-range interactions in non-equilibrium statesare expected (correlation) and the thermodynamics deviate from the Boltzmann-Gibbs formalism. Emphasis is given to background earthquakes since it is generally agreed that aftershock sequences comprise correlated sets. Accordingly, the analysis is based on the accurate earthquake catalogue compiled of the South California Earthquake Data Center, in which aftershocks are either included or have been removed with a stochastic declustering procedure. We examine multivariate cumulative frequency distributions of earthquake magnitudes, interevent time and interevent distance, in the context of Non-Extensive Statistical Physics, which is a generalization of extensive Boltzmann-Gibbs thermodynamics to non-equilibrating (non-extensive) systems. The results indicate a persistent subextensive seismogenetic system exhibiting long-range, moderate to high correlation. Criticality appears to be a plausible causative mechanism although conclusions cannot be drawn until alternative complexity mechanisms can be ruled out.